(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
While existing studies predominantly focus on national-level export performance, the regional dimension of export potential remains insufficiently explored, particularly in transition and emerging economies. In the context of increasing global trade fragmentation and heightened competition in international markets, enhancing regional export potential has become a critical priority for emerging economies